Pengaruh Lokasi dan Fasilitas terhadap Keputusan Berkunjung di Objek Wisata Goa Maria Tritis - Enny Mulyantari (Media Wisata, 2020)
Maria Tritis Cave is a holy place that has its uniqueness, a natural cave and has the beauty of stalagmites and stalagmites in it. This cave is located in the southern way, which is the way to get to some of the beaches in Gunungkidul. Besides being a beautiful cave, Maria Tritis Cave also has various supporting facilities for holy tours. Easy location and complete facilities will enhance the tourist’ decision to visit. The sampling technique was done by an accidental sampling of 100 archipelago tourists visiting tourists attraction of Maria Tritis Cave Gunungkidul. Methods of data collection use documentation and questionnaires, data analysis with instrument tests (validity and reliability tests), and partial or simultaneous our multiple regression analysis using SPPS for Windows version 16. The results showed that the location and facility variables significantly influence tourist’ visiting decision. Location and facility variables influence jointly the decision of archipelago tourists in visiting Maria Tritis Cave Gunungkidul. Suggestions from the research, the managers should pay attention to matters that are relating to the location such as the access to the cave and the clear directions from/to the cave, add facilities that support outbound activities and maintain existing facilities